God on the big screen: a cinematic history of prayer from the silent era to today - Lindvall, Terry (New York University Press, 2019)
Silent prayers (1902-1927) -- Censored prayers (1927-1939) -- Foxhole prayers (1939-1945) -- Postwar secular prayers (1946-1963) -- Cynical prayers (1964-1976) -- Revival of prayer (1976-1988) -- Postmodern prayer (1989-2000) -- Millennial prayers (2000-2017).